PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP HARGA SAHAM PADA PT. ANEKA TAMBANG TBK PERIODE 2012-2021 - Nani Rusnaeni; Tri Wartono; Agus Supriatna (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze the effect of the variable Return On Assets and Current Ratio on Stock Prices at PT. Aneka Tambang Tbk. Period 2012-2021. The research method used is quantitative and uses statistical analysis and financial ratios. The population used is the financial statements of PT. Aneka Tambang Tbk. 2012-2021 years. Based on the results of the study, it shows that the variable Return On Assets partially (t test) obtains a tcount value of 0.886 < ttable 2.365 with a significance value of 0.405 > 0.05, which means that there is no partial effect between Return On Assets on Stock Prices. And the Current Ratio variable obtains a tcount value of 0.351 < ttable 2.365 with a significance value of 0.736 > 0.05, which means that there is no partial effect between the Current Ratio variable on stock prices. Simultaneously (Test F), the variable Return On Assets and Current Ratio obtained a value of Fcount 1.020 < Ftable 5.59 with a significance of 0.409 > 0.05 thus Ho3 is accepted and Ha3 is rejected, which means that simultaneously there is no influence between Return On Assets and Current Ratio to Stock Price. From this study, it was obtained that the R square value was 0.226 x 100% or 22.6%, which means that the Return On Assets and Current Ratio simultaneously influence 22.6%, while the remaining 77.4% is another factor.